Retrospective Study of the Epidemiological-Clinical Characteristics of Burns Treated in a Hospital Emergency Service (2018-2022) - María Alcalá-Cerrillo; Josefa González-Sánchez; Jerónimo J. González-Bernal; Mirian Santamaría-Peláez; Jessica Fernández-Solana; Sara M. Sánchez Gómez; Ana Gómez-Martín (MDPI AG, 2024)
Background: Burns are a common and severe medical emergency requiring immediate specialized care to minimize damage and prevent complications. Burn severity depends on depth, extent, and location, with more complex care needed for burns on critical areas or extensive burns. Nursing is essential in burn management, providing immediate care, adapting treatments, managing pain, preventing infections, and offering emotional support for recovery. The study aims to analyse the epidemiological and clinical characteristics of burns treated at the Hospital Emergency Department of the Hospital Complex of Cáceres (Spain) from January 2018 to December 2022. It looks at factors like gender, age, hospital stay duration, emergency type (paediatric or adult), main diagnosis, skin thickness, burn degree, affected body areas, percentage of body surface area burned, and treatment types. It also investigates how treatment varies by gender, age, skin thickness, and burn severity. The relevance of this research lies in the fact that periodic epidemiological studies are essential to monitor changes in diseases, evaluate the effectiveness of interventions, detect outbreaks quickly, update knowledge on risk factors, and guide health policy decisions. This ensures an adapted and effective response to the needs of the population. Methods: Retrospective, observational study that analysed burn cases treated at the Hospital Complex of Cáceres (Spain) 2018-2022. Inclusion criteria were based on ICD-10 codes for burns, excluding severe cases not treated in this service. Data were analysed using descriptive statistics, Student's t-tests, Chi-square tests, and ANOVA. Results: 220 patients surveyed, with a mean age of 47 years and 60.9% male. Most burns (95.5%) affected the external body surface, with a mean hospital stay of 7.86 days. Medical treatment was provided to 75.5% of patients, and 24.5% required surgical intervention. Significant differences in treatment procedures were observed according to age, skin thickness, and burn degree. Older patients had more procedures and longer hospital stays. Excision and transfer procedures were more common in full-thickness and severe burns. Conclusions: The findings align with previous research on burn demographics and treatment approaches. Treatment differences by age and burn severity highlight the need for tailored interventions. The study underscores the importance of comprehensive burn management, including psychological support for improved long-term outcomes. Further research could explore the impact of socio-economic factors on burn incidence and treatment. This study was not registered.